An Investigation of Ecotourism Code of Conduct A Comparative Study Between Thai and Malaysian Tour Operators - Sangpikul, Aswin (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 3 (2558): September - December 2015, 2015)
This study has an objective to examine and compare ecotourism practices between Thai and Malaysian tour operators. The six key elements of ecotourism (i.e. Nature, Education, Impact, Conservation, Community and Corporate Elements) together with the ecotourism code of conduct are employed as a framework to investigate the practices of tour operators. The samples being investigated are two tour operators based in Phuket and the other two in Penang. Participant observation and in-depth interview were used to collect the required data. Data were content analyzed to determine how the tour operators conduct their tours and to find out whether their practices correspond to the ecotourism code of conduct. The findings revealed that Thai and Malaysian tour operators have conducted their tours mainly corresponding to ecotourism code of conduct. However, some practices seem to be less attended by the operators and are not congruent with the ecotourism concept. Suggestions are given to improve their tour performances and to enhance a sustainable tourism business.              Keywords: Ecotourism, Code of Conduct, Tour Operators, Thailand, Malaysia, AEC
Keywords: Ecotourism, Code of Conduct, Tour Operators, Thailand, Malaysia, AEC